Health problems among the street children of Dharan municipality - Thapa, K; Ghatane, S; Rimal, SP (Kathmandu University Medical Journal, 2010)
Background: The street children, a marginalised and vulnerable population to poor health, have grown all over the world and also in our country. The continuous exposure to harsh environment and nature of their life style threatens their mental, physical, social and spiritual well being. With the increasing number the problem is also growing at an alarming proportion. It is therefore important to have baseline data on their health problems. Objectives: This study was conducted to identify the physical health problems among the street children of Dharan Municipality, Nepal. Materials and methods: This is a cross sectional descriptive study. Forty eight subjects were included in the study. Research instruments included an interview schedule, physical health examination performa and lab investigations (i.e. blood for haemoglobin, urine routine examination/microscopic examination, stool routine examination/ microscopic examination). Results: Study results showed that 68.8% of the street children were between 11-15 years of age, 95.8% were males. Out of the total subjects 81.2% were found to be rag pickers. Research findings reveal that 100% of the subjects had at least one or more health problems. The study revealed that majority 87.5% had the habit of cigarette smoking, 50% had habit of consuming alcohol and 72.9% had the habit of taking drug. Dendrite (glue sniffing) was the only drug used by the respondents in this study. The most common health problems were head lice infestation (81.2%), headache (66.7%), cut injury (60.4%), common cold (52.1%), dental caries (52%), burning micturation (47.9%), cough (47.9%), underweight (43.8%), abdominal pain (39.6%), tinnitus (37.55%), gum bleeding (33.3%), joint pain (31.2%), eye infl ammation (25%), leg cramps (25%), palpable lymph nodes (25%), chest pain (18.8%), skin lesions (16.7%), abnormal vision (8.3%). Conclusion: Most of the diseases were due to poor health habits. It was found that the nature of work, their life styles and the different types of behaviour they adapt finally lead them to many health problems. The health problem can be prevented, if an integrated program that involves all the issues are developed and implemented. Key words: Street children; health problems; Dharan. DOI: 10.3126/kumj.v7i3.2737 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 272-279